ChemInform Abstract: Ionic Liquids in Transition Metal‐Catalyzed Hydroformylation Reactions. Issue 39 (September 2016) - Rieger, Bernhard; Plikhta, Andriy; Castillo‐Molina, Dante A.
Abstract: Review: 192 refs.